Cover Feature: Cobaloxime Complex Salts: Synthesis, Patterning on Carbon Nanomembranes and Heterogeneous Hydrogen Evolution Studies (Chem. Eur. J. 68/2021). Issue 68 (12th November 2021) - Oswald, Eva; Gaus, Anna‐Laurine; Kund, Julian; Küllmer, Maria; Romer, Jan; Weizenegger, Simon; Ullrich, Tobias; Mengele, Alexander K.; Petermann, Lydia; Leiter, Robert; Unwin, Patrick R.; Kaiser, Ute; et al.
Abstract : The setup for operando measurement of hydrogen evolution under illumination is shown in the cover feature picture. Various cobaloxime catalysts were deposited onto solid support (carbon nanomembranes) and evaluated with respect to their hydrogen evolution reaction by using Pd microsensors. The structure of the most efficient cobalt‐based double salt complex is depicted in the foreground. More information can be found in the Full Paper by M. von Delius, C. Kranz, et al. (DOI: 10.1002/chem.202102778 ). Photo credit: Elvira Eberhardt, Ulm University.